Mutagenic and cytotoxic activity of an isocoumarin (paepalantine) isolated from Paepalanthus vellozioides - Varanda, Eliana Aparecida [UNESP]; Raddi, Maria Stella Gonçalves; De Luz Dias, Francisca; Araújo, Maria Cristina P.; Gibran, Solange Cardoso Alvares; Takahashi, Catarina S.; Vilegas, Wagner (My University, 1997)
A new isocoumarin with antimicrobial activity was isolated from Paepalanthus vellozioides (a native Brazilian plant) and called paepalantine. This study was carried out to assess the mutagenic activity of this new agent in assays with Salmonella typhimurium TA100, TA98, and TA102 and in Chinese hamster ovary (CHO) cell cultures, as well as cytotoxicity to McCoy cells. Paepalantine caused a significant dose-dependent increase in the frequency of revertants in the three strains used in the assay, both with and without S9 mix, in concentrations varying from 2 to 128 μg/plate. The mutagenicity was confirmed in assays with CHO cells treated in the G1, S, and G2 phases of the cell cycle. There was an increase in the chromosomal aberration frequency, mainly in the G2 phase. Furthermore, the mitotic index of the treated cultures (40, 80, and 160 μg/ml) was significantly lower, indicating cytotoxicity. The midpoint cytotoxicity values to McCoy cells by the neutral red (NR) and microculture tetrazolium (MTT) techniques resulted in a NR50 and MTT50 of 30 and 38 μg/ml, respectively. Alterations to the paepalantine structure are suggested to reduce its mutagenic and cytotoxic activity in investigations for its antineoplasic potential.
Keywords: Ames test; Chromosomal aberrations; Cytotoxicity; Isocoumarin; Paepalantine